Administrative creativity and job performance: An Empirical Study at Jadara University - Masa'd, Fawzieh; Aljawarneh, Nader Mohammad (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to identify the reality of administrative creativity and its effect on the job performance of administrative employees at Jadara University. To meet this aim, a questionnaire was prepared and distributed to 100 administrative employees and 88 questionnaires ready for analysis, were backed and 88 % was the returning percentage. Data were analyzed by using SPSS statistical program and suitable statistic tests were done to reach the results of the study. The result of this study showed that there is a positive relationship between creative capabilities (originality, ability to analyze, acceptance of risk, fluency and mental flexibility), and job performance. Recommendations for creative capabilities and job performance are discussed